From Bench to Bedside: Evaluation of AHCC Supplementation to Modulate the Host Immunity to Clear High-Risk Human Papillomavirus Infections - Smith, Judith A.; Mathew, Lata; Gaikwad, Anjali; Rech, Barbara; Burney, Maryam N.; Faro, Jonathan P.; Lucci, Joseph A.; Bai, Yu; Olsen, Randall J.; Byrd, Teresa T. (Frontiers in Oncology, 2019)
Objective: There is currently no effective medicine or supplement for clearance of high risk- human papillomavirus (HR-HPV) infections. We have taken a systematic approach evaluating the potential use of AHCC supplementation to support clearance of HR-HPV infections. The primary objective of this research was to evaluate AHCC supplementation to modulation of the host immune system to clear HR-HPV infections from bench to bedside. Methods: Cervical cancer cells, CaSki (HPV16+), HeLa(HPV18+), SiHa(HPV16/18+), and C-33A(HPV−), were treated in vitro with AHCC 0.42 mg/mL daily x7 days then observed x7 days with daily sample collection. A confirmatory study in cervical cancer mouse models, SiHa(HPV16/18+) and C-33A(HPV−), was conducted: mice were divided into three groups per cell line then dosed with AHCC 50 mg/kg/d (N = 10), or vehicle alone (N = 10), or no supplementation (N = 10) for a total of 90 days followed by 30 days of observation. Tumors were measured 3x/week and blood samples collected bi-weekly to evaluate interferon (IFN) alpha(α), beta(β), and gamma(γ) and immunoglobulin G(IgG) by immunoassays. Tumors were evaluated for HR-HPV expression by PCR. Two pilot studies of 10 patients each were conducted in women with confirmed persistent HR-HPV+ infections. The 1st study evaluated AHCC 3g from 5 weeks up to 6 months and 2nd study evaluated AHCC 1g < 8 months. HR-HPV DNA status and the immune panel were monitored at each visit. Results: HR-HPV clearance was observed in vitro and confirmed in the animal studies as a durable response. Four of six (66.7%) patients had confirmed HR-HPV clearance after 3–6 months of AHCC 3g. Similarly, 4 of 9 (44%) patients had confirmed HR-HPV clearance after 7 months of AHCC 1g. Suppression of IFNβ <25 pg/mL was observed in those clearing the HR-HPV infection. Conclusion: Pre-clinical in vitro and in vivo studies demonstrated durable clearance of HR-HPV infections. The preliminary data from the two pilot studies suggested that AHCC supplementation supports the host immune system for successful clearance of HR-HPV infections. A confirmatory phase II randomized, double-blinded, placebo-controlled study is ongoing.